GRP-063 Evaluation of Intravenous Immunoglobulin (IVIG) Prescriptions in an Italian Paediatric Hospital: An Overview of Off-Label Uses. (12th March 2013) - De Meo, MS; Pompilio, A; Ciuccarelli, F; Andresciani, E; Garzone, A; Mannucci, A; Moretti, V
Abstract : Background: Our paediatric hospital 'G. Salesi' officially follows regional guidelines on the proper use of IVIG. Guidelines aim to improve the management of drug requests during times of shortage and to ensure IVIG supplies for critical situations. Purpose: To evaluate the suitability of IVIG prescriptions for children, to identify 'off-label' uses, to cheque the amounts of drug used. Materials and Methods: Retrospective analysis of prescriptions delivered to the hospital pharmacy from July 2011 to June 2012. IVIG requests were paper forms with 7 licenced directions according to regional guidelines: primary immune-deficiency disorder (PID), myeloma/chronic lymphocytic leukaemia (CLL), idiopathic thrombocytopenic purpura (ITP), Kawasaki disease (KD), Guillain–Barré syndrome (GBS), bone marrow allograft (BMAG) and severe bacterial infectious disease (BID). Results: We examined 154 drug requests for 67 patients admitted to one or more of the following wards: Onco-haematology, Paediatrics, Infectious Diseases Unit, Neonatology, Intensive Care Unit, Paediatric Neuropsychiatry. One patient was also affected by cystic fibrosis (CF). Onco-haematology was the most demanding ward with 98 prescriptions, 46 patients and 58% (2430 g/4160 g) of dispensed IVIG. The CF patient with ITP received 580 g with 14 prescriptions over 6 months. Most of the requests had licenced indications (131) classified as follows: BID (68), ITP (26), PID (23), KD (11), GBS (1) and BMAG (1). Eighteen patients had 23 off-label requests. The main unlicensed uses were thrombocytopenia (6), hypogammaglobulinaemia in acute lymphoblastic leukaemia (5), autoimmune haemolytic anaemia (3), neonatal hyperbilirubinaemia (2) and Rh iso-immunisation (1). Seventeen off-label prescriptions didn't have written clinical certification to support the request. However the request form declared the physician's responsibility and the absolute necessity of IVIG treatment. Conclusions: Despite regional guidelines, off-label use of IVIG is constant in our hospital. Hospital pharmacists should work more closely with clinicians to identify off-label prescriptions without evidence/directions because this drug can be life-saving and it is necessary to keep it available for critical situations. No conflict of interest.